The Artist as Educator: Challenges in Museum-Based Residences. - Pujol, Ernesto (Art Journal)
Focuses on the museum-based residencies of visual artists. Educational goals of the residencies; Contributions of open-process residencies; Relevance of developing new models for museums, artists and communities.